2019
DOI: 10.1038/s41598-019-39985-7
|View full text |Cite
|
Sign up to set email alerts
|

Distal interphalangeal joint extensor tendon enthesopathy in patients with nail psoriasis

Abstract: The aim of the study was an ultrasound assessment of distal interphalangeal (DIP) joint enthesopathy in patients with nail psoriasis. Altogether, 72 patients with nail psoriasis (41 with psoriasis and 31 with psoriatic arthritis) and 30 people in the control group participated in the study. In total, 1014 nails were examined. The thickness of DIP digital extensor tendons in the groups of patients with psoriasis (Ps) and psoriatic arthritis (PsA) was correlated with the nail bed thickness (r = 0.316, p = 0.027 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…[12][13][14][15][16][17] These findings are supported by the growing evidence for an anatomical correlation between nail psoriasis and enthesitis of the DIP joints, as a manifestation of PsA. 18,19 Besides a higher psoriasis severity, 4 a longer duration of psoriatic skin lesions is also associated with a higher frequency in nail changes. 20 The relatively long duration of disease could partly account for the high prevalence of nail changes in our population.…”
Section: Discussionmentioning
confidence: 82%
“…[12][13][14][15][16][17] These findings are supported by the growing evidence for an anatomical correlation between nail psoriasis and enthesitis of the DIP joints, as a manifestation of PsA. 18,19 Besides a higher psoriasis severity, 4 a longer duration of psoriatic skin lesions is also associated with a higher frequency in nail changes. 20 The relatively long duration of disease could partly account for the high prevalence of nail changes in our population.…”
Section: Discussionmentioning
confidence: 82%
“…Nail disease in psoriasis has been correlated with the presence of enthesopathy and psoriatic arthritis, even in the absence of clinical signs. Therefore, with clinically inconclusive signs of a psoriatic onychopathy, US may add useful information [50][51][52].…”
Section: Psoriasismentioning
confidence: 99%
“…The related report indicated that one of the pathogeneses of psoriasis is hypernomic activation of toll-like receptors in dendritic cells, which is basically believed to be crucial in initiating an immune response ( Meng et al, 2017 ). To date, most studies have investigated feasible treatments for the disease, which may require the fundamental role for short-term improvement and long-term control, but there is no standardized therapeutic regimen for psoriasis and is incapable of resulting in the complete clearing of psoriasis ( Al-Suwaidan and Feldman, 2000 ; Naldi et al, 2003 ; Krajewska-Wlodarczyk et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%